John Wilkins: The Boastful Chef The Discourse of Food in Ancient Greek Comedy - Davidson, Alan E (Petits Propos Culinaires, 2024)
John Wilkins: The Boastful Chef The Discourse of Food in Ancient Greek Comedy. Oxford University Press, 2001 : ISBN 0-19-924068-X: 465 pp., bibliography, indexes, h/b, £55.